Web-Based Music Study in Boosting Active Listening - Maharsiwi Diah Chandra Dewi; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2020)
The purpose of this research was to prove that using a web-based music study is effective in boosting active listening. This research conducted in Private Elementary School Khalifa IMS Tangerang Selatan. The population of this research is third-grade students, and the sample is P3C consists of 25 students. The method of this research is quantitative method and using pre-experimental design. To collect the data, the writer used a pre-test, and post-test that given to the students. The resulting score of the data indicated that, the total score of students in the pre-test was 1338 with the average were 53.52. The lowest score of the pre-test was 37 and the highest score was 60. The total score of students in the post-test was 2211 with the average were 88.44. The lowest score of the post-test was 80 and the highest score was 97. It is significantly different from the result of pre-test and post-test scores. The results of the pre-test and post-test were calculated by using manual statistically. The calculation indicated that t – observe were 4.79 with t – tables were 1.70 and the significance 0.05. Therefore, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. The writer concluded that using Web-based music studies in teaching English was effective to improve students’ listening skills.